Improving Clay Brick Column’s Compression Capacity using CFRP Sheets and Reinforced Concrete Jacketing - Dakhil, Ammar; Naji, Zahir; Al Jasim, Samir (Iraqi Journal of Civil Engineering, 2022)
Brick as a construction material can be considered one of the most common materials used for a very long time to construct buildings in iraq. The historic building represents one of the most important figures representing the rich history of iraq, which is built with bricks. Due to the aging of this type of building, a necessary improvement and retrofit need to occur. The paper investigates the ability to use different kinds of materials such as cfrp and srg to enhance the brick columns’ structural capacity. From the results and discussions, it can be concluded that these materials are suitable to be used for this purpose with some limitations due to brick capacity itself.